The “Cancer Bush” Sutherlandia (syn. Lessertia) frutescens. An Example of Promotional Research, or Is There Scientific Merit? - Gernandt, Nicezelle; van der Kooy, Frank (Planta Medica, 2025)
Sutherlandia (syn. Lessertia) frutescens is indigenous to the drier regions of southern Africa. Sutherlandia frutescens has a long history of traditional medicinal use and is credited with antiviral, antibacterial, antifungal, and anticancer properties. It is a very popular phytomedicine and, as the common name implies, is used as a prophylaxis and treatment of cancer. The objective of this review was to collate all published scientific data on the genera Sutherlandia and Lessertia regarding their antiproliferative properties and critically evaluate the data against established guidelines. Despite its use as traditional medicine, the potential of S. frutescens as a cancer treatment remains highly questionable. While in vitro studies suggest some potential antiproliferative effects, many studies lack positive controls and selectivity studies or use excessively high dosages, well above established guidelines, translating into unrealistic clinical applications. Consequently, these studies often appear overly optimistic and biased. Very few well-designed studies are available, and most research fails to meet established guidelines for evaluating selective cytotoxicity. Given these limitations and the absence of rigorous in vivo studies and/or clinical trials, future research may first focus on identifying chemovars with acceptable bioactivity and/or investigating the possibility of the presence of prodrugs by simulated gastrointestinal tract studies. Based on available data, it must be concluded that S. frutescens does not exhibit acceptable levels of bioactivity/selectivity, and keeping in mind possible herb-drug interactions and the serious nature of cancer, which causes over 10 million deaths annually, S. frutescens should not currently be recommended for use.
Keywords: anticancer; cytotoxic; Fabaceae; herbal medicine; marketing; Sutherlandia frutescens; traditional remedy